ELECTRICAL AND MAGNETIC PROPERTIES OF MULTIFERROIC Co0.6Zn0.4Fe1.7Mn0.3O4 DOPED 0.99Bi0.47Na0.47Ba0.06TiO3-0.01Ba(Sn0.70Nb0.24)O3 CERAMICS SYNTHESIZED VIA THE SOLID-STATE COMBUSTION TECHNIQUE - Luangpangai, Anupong; Chuai, Phomphon; Rittidech, Aurawan; Pinitsoontorn, Supree; Jantaratana, Pongsakorn; Vittayakorn, Naratip; Udeye, Thanya; Bongkarn, Theerachai (My University, 2025)
Multiferroic (1-x)[0.99Bi0.47Na0.47Ba0.06TiO3-0.01Ba(Sn0.70Nb0.24)O3]-xCo0.6Zn0.4Fe1.7Mn0.3O4 (abbreviated as BNBT-BSN-xCZFMO) ceramics with x ranging from 0 to 0.20 were fabricated using the solid-state combustion technique. The effect of varying BNBT-BSN: CZFMO ratios on the phase structure, microstructure, electrical and magnetic properties was investigated. X-ray diffraction (XRD) analysis of pure BNBT-BSN showed a perovskite structure with rhombohedral and tetragonal phases. The doped BNBT-BSN-xCZFMO ceramics displayed coexisting rhombohedral, tetragonal, and cubic spinel phases, with the cubic spinel phase increasing when the CZFMO content increased. In addition, the XRD peaks shifted to higher angles as the CZFMO content increased, indicating a decrease in lattice parameters. The dielectric constant decreased with higher CZFMO content and higher frequencies. The pure BNBT-BSN ceramic exhibited a saturated P-E loop with a Pmax of 33.2 µC/cm2, Pr of 26.1 µC/cm2, and an Ec of 14.5 kV/cm. With increased CZFMO content, non-saturated and bloated P-E loops with lower Pmax, Pr, and Ec were observed, implying a rise in the leakage current. The addition of CZFMO induced ferromagnetic behavior in the ceramics, leading to an increase in Ms and a reduction in Hc as CZFMO content increased. The magnetoelectric coupling coefficient of BNBT-BSN-xCZFMO ceramics continuously increased with higher CZFMO content.
Keywords: BNBT-BSN-xCZFMO; Dielectric; Ferroelectric; Ferromagnetic; Phase Structure